Lithofacies and reservoir characteristics of the Lower Cretaceous continental Shahezi Shale in the Changling Fault Depression of Songliao Basin, NE China. (December 2018) - Gao, Fenglin; Song, Yan; Li, Zhuo; Xiong, Fengyang; Chen, Lei; Zhang, Yinghan; Liang, Zhikai; Zhang, Xinxin; Chen, Zhiyuan; Joachim, Moortgat
Abstract: The increasing enthusiasm for continental shale gas exploration in China has made the Shahezi shale in the Changling Fault Depression an important research target due to its impressive demonstrated gas capacity. In this work, geochemical and petrologic analyses, field emission-scanning electron microscopy (FE-SEM) observation, low-pressure adsorption isotherms and mercury intrusion porosimetry (MIP) were conducted on 19 core samples to comprehensively analyze the reservoir characteristics of different lithofacies. The results show that the Shahezi shale has the characteristics of low content of organic matter (OM), high Ro, high content of clay minerals and small fractions of calcite. The kerogen is type III, dominated by vitrinite and inertinite. Clay minerals are dominated by the mixed illite-smectite, followed by illite and a small amount of chlorite. The Shahezi shale develops three kind of stratification structures according to the thickness of laminae: laminated structures, bedded structures, and massive structures. On the basis of TOC, mineral composition and petrologic texture, eight types of lithofacies were recognized. The organic pores show strong heterogeneity and are poorly developed, while clay-related pores are ubiquitous. The Shahezi shale has a high pore volume (PV) (0.005–0.031 ml/g, averaging 0.0173 ml/g) and specific surface area (SSA) (2.57–27.48 m 2 /g, averaging 16.61 m 2 /g), indicating an excellent storage capacity. Low-pressure CO2 and N2 isotherms and MIP were utilized to construct the whole-range pore size distribution (PSD). Based on the whole-range PSDs, mesopores were observed to contribute most to the PV, followed by macropores. Micropores and mesopores account for more than 99% of SSA. The reservoir capacity of different lithofacies is following the order in terms of PV and SSA, from high to low: organic-medium massive mixed shale (OMMMS), organic-medium massive argillaceous shale (OMMAS), organic-rich laminated argillaceous shale (ORLAS), organic-medium laminated argillaceous shale (OMLAS), organic-rich bedded mixed shale (ORBMS), organic-rich bedded siliceous shale (ORBSS), organic-medium bedded argillaceous shale (OMBAS), organic-poor shale (OPS). The main controlling factors of pore structure for the Shahezi shale are clay minerals rather than OM, which is similar to the continental Chang 7th shale but contrary to the Longmaxi shale. However, the Shahezi shale is mainly of low TOC and strong heterogeneity pores development result from OM macerals, while the Chang 7th shale is mainly of low maturity. Ro play an important role in promoting pore development. Only high content of calcite can greatly improve the pore space due to its solubility. This work contributes to the theory of continental shales and how to identify continental high-quality shale reservoirs. Highlights: Reservoir characteristics of eight types of lithofacies is fully investigated. Dominant controlling factors of Shahezi shale are clay minerals rather than TOC. Strong heterogeneity of organic pores is attributed to different OM macerals. Shahezi shale have relative high storage capacity compared with shales in other environments.